2017
DOI: 10.18203/2320-6012.ijrms20174596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and hepatitis C virus infection in repeatedly transfused thalassemics in a tertiary care hospital in eastern India

Abstract: Background: Patients of thalassemia who are conventionally treated by a regular transfusion regimen are at a risk of developing transfusion transmissible infections, including hepatitis. The present study was conducted to assess the prevalence of hepatitis B and hepatitis C virus infections among repeatedly transfused thalassemia patients.Methods: A total of 207 patients of beta-thalassemia, who had received at least 10 transfusions were tested for hepatitis B surface antigen (HBsAg) and anti-HCV antibody usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The present study showed comparable results as described by Choudhury et al 2001, 19 and Mukherjee et al, 2017. 22 Furthermore anti-HCV seropositivity in our patients (51%) was comparable among multitransfused patients in Jordan (40%), 23 Egypt (45% to 76%), 24 Iran (44.7%), 25 and Pakistan (51.3%). 26 In our study, the seropositivity of HBsAg among thalassemic children was 1.5%.…”
Section: Hepatitis C Virus (Hcvsupporting
confidence: 60%
See 1 more Smart Citation
“…The present study showed comparable results as described by Choudhury et al 2001, 19 and Mukherjee et al, 2017. 22 Furthermore anti-HCV seropositivity in our patients (51%) was comparable among multitransfused patients in Jordan (40%), 23 Egypt (45% to 76%), 24 Iran (44.7%), 25 and Pakistan (51.3%). 26 In our study, the seropositivity of HBsAg among thalassemic children was 1.5%.…”
Section: Hepatitis C Virus (Hcvsupporting
confidence: 60%
“…Our result was comparable to a study in India, where the prevalence rate of HBsAg was ranged from 1.2–7.4%. 22 However, the prevalence rate is still high compared to other Asian countries, such as Turkey and Malaysia, which reported lower HBsAg seroprevalence rates of 0.75% and 1%, respectively. 27 , 28 Differences in the prevalence of TTIs amongst thalassemic could be related to geographical differences in the prevalence of the viral infections among blood donors, the nature of blood donors, whether replacement or voluntary and most important the nature of care individual thalassemics receives.…”
Section: Discussionmentioning
confidence: 94%
“…When compared to statistics available through peer-reviewed studies from India,[ 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] incidence of HIV-1, HBV and HCV in our thalassemia cohort was on the higher side [ Table 7 ]. Most recent reports from our country document the high prevalence of these TTIs due to the use of molecular tests in addition to serological tests like in our study [ Table 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also contraindicating reports on the rate of prevalence in studies conducted in different parts of the world, for example, the prevalence of HCV among Egyptian, Taiwanese, Thai, Italian, Jordanian, Pakistan and eastern India thalassemia patients was reported 45.50%, 37.30%, 20.20%, 56.30%, 40.5%, 49% and 24.6%, respectively [57][58][59][60][61][62][63]. Although our overall prevalence is lower than these reports, most of the studies we have reviewed is consistent with the mentioned studies from the other countries.…”
Section: Discussionmentioning
confidence: 99%